THE PAMPA BLANCA PROPERTY IN THE TAMBO VALLEY FAMILY, PROPERTY AND PRODUCTION, 1856 -1971 - Eguiluz Menendez, Percy (2023)
The Pampa Blanca hacienda in the Tambo valley arose in the mid-19th century, when the farm of the same name was acquired by Juan Guillermo Lira, beginning the history of this hacienda, later passing the property to his son Víctor F. Lira, the philanthropist, who will modify its position in one of the most important in Arequipa. The Pampa Blanca farm was part of the old Chucarapi hacienda, whose origins date back to the 17th century. This study aims to make known the geographical aspect of the Tambo river and valley, the presence of the Lira family in this valley and in the city of Arequipa, the historical process of the formation of the Pampa Blanca hacienda and the extension owned by the He mentioned family, production and relations with workers, and the agro-industrial economic enclave that was established in this part of the Tambo Valley until its decline with the agrarian reform of the government of General Velazco Alvarado.